Exploring Non-Motherhood: Analysis of Perceived Factors in Feminist Women, Mothers, and Non-Mothers - Rosa María Mañas Migal; Montserrat Monserrat Hernández; Ángeles Arjona Garrido (Sexes, 2025)
Questioning motherhood as a social mandate has been one of the main objectives of feminism. Motherhood has traditionally been linked to the idea of femininity and the reproductive function, which has led to women being thought of as “compulsory mothers”. However, this idea is currently changing, despite the fact that judgment is exercised on non-mothers. This research is part of a cross-sectional descriptive study, whose objective is to analyze the barriers and incentives to childbearing in the female population. A questionnaire was designed and administered to a representative sample of 318 women who were selected for our analysis, with a confidence level of 95% and a margin of error of 5%. Results: Economic motives correlate positively with other variables, as well as work motives, the couple’s decision to not want to have children, and not having a stable partner, which suggests that these women have different motives for choosing not to have children. The main conclusions are that social and family pressures appear to have a limited impact on the decision not to have children, suggesting a change in social norms and expectations about the role of women in society, as women continue to gain autonomy and control over their reproductive decisions.